Copy number variation of MYLK4 gene and its growth traits of Capra hircus (goat). Issue 6 (11th November 2020) - Shi, Shu-Yue; Li, Li-Juan; Zhang, Zi-Jing; Wang, Er-Yao; Wang, Jian; Xu, Jia-Wei; Liu, Hong-Bing; Wen, Yi-Fan; He, Hua; Lei, Chu-Zhao; Chen, Hong; Huang, Yong-Zhen
Abstract: Copy number variation (CNV) is a form of genetic variation caused by genome rearrangement, with abnormal fragments ranging from 50 bp to Mb. And, CNV is closely related to disease, growth and reproductive shape of livestock. As a member of myosin light chain kinase ( MYLK ) family with serine/threonine specificity, MYLK4 belongs to an enzyme encoded by MYLK4 gene. Although MYLK4 is a recognized kinase, its function has yet to be revealed in subsequent studies. This study aims to analyze CNV and genetic effects of MYLK4 gene in goats. We used qPCR to detect CNV of MYLK4 gene in African Nubian goat ( n = 32), Guizhou black goat ( n = 196) and Guizhou white goat ( n = 95), respectively, and correlated CNV data of MYLK4 gene with goat growth traits in Chinese goats. The results showed that the effect of MYLK4 gene CNV on body weight, body length and body height of goats had significantly different ( p < 0.05, Q < 0.05), in which CNV showed better growth traits in type of deletion. Therefore, CNV of MYLK4 gene can be used as a molecular marker for assisted selection of goat growth traits, which provides a theoretical basis for the genetic improvement of goat breeds in China.